High-performance InP/InGaAs heterojunction bipolar phototransistors for optoelectronic applications - Jihane Ouchrif; Abdennaceur Baghdad; Aicha Sahel; Abdelmajid Badri (Institute of Advanced Engineering and Science, 2023)
Phototransistors are attractive devices for applications in optical fiber telecommunication systems. They are used for the detection of optical signals and the amplification of these signals. This paper presents an investigation of how the technological parameters of indium phosphide (InP)/indium gallium arsenide (InGaAs) heterojunction bipolar phototransistor can impact its responsivity at two wavelengths, 1310 nm and 1550 nm. Based on the results of this investigation, we proposed optimized structures for the studied phototransistor. In this work, we used the software technology computer aided-design (TCAD)-Silvaco to simulate the physical and the electrical behavior of the different structures. The proposed optimized phototransistors can be used for various optoelectronic applications.